City of dragons - Hobb, Robin., Author (Hobb, Robin. Rain Wilds chronicles, 2012)
Accompanied by human keepers, the dragons embark on a dangerous journey to their ancient, mythical homeland of Kelsingra, and along the way form deep bonds with the humans that are severely tested during the journey's final days.